Attention But Not Awareness Modulates the BOLD Signal in the Human V1 During Binocular Suppression - Watanabe, Masataka; Cheng, Kang; Murayama, Yusuke; Ueno, Kenichi; Asamizuya, Takeshi; Tanaka, Keiji; Logothetis, Nikos (Science (American Association for the Advancement of Science), 2011)
Although recent psychophysical studies indicate that visual awareness and top-down attention are two distinct processes, it is not clear how they are neurally dissociated in the visual system. Using a two-by-two factorial functional magnetic resonance imaging design with binocular suppression, we found that the visibility or invisibility of a visual target led to only nonsignificant blood oxygenation level-dependent (BOLD) effects in the human primary visual cortex (VI). Directing attention toward and away from the target had much larger and robust effects across all study participants. The difference in the lower-level limit of BOLD activation between attention and awareness illustrates dissociated neural correlates of the two processes. Our results agree with previously reported V1 BOLD effects on attention, while they invite a reconsideration of the functional role of V1 in visual awareness.